Intraoperative nerve monitoring in endocrine surgery: prevalence and reasons for its use in Australia and New Zealand. Issue 5 (30th October 2019) - Leong, David Chee Weng; Lo, Johnny; Ryan, Simon; Nguyen, Hieu; Lisewski, Dean
Abstract: Background: Intraoperative nerve monitoring (IONM) has increasingly been used in thyroid surgery by general, endocrine and head and neck surgeons. The purpose of this paper was to explore the prevalence and reasons for the usage of IONM in endocrine surgery in Australia and New Zealand. Methods: A survey was sent to general surgeons registered with the Royal Australasian College of Surgeons involved in endocrine surgery and members of the Australian and New Zealand Endocrine Surgeons. Users were divided into surgeon type, area of work, hospital type and volume of surgery. These data were analysed with univariate and multivariate logistic regression models. Results: Significant differences in IONM usage levels were observed between endocrine and general surgeons, area of work and volume of surgery performed. Endocrine surgeons are significantly more likely to use IONM than general surgeons. Surgeons who work in tertiary hospitals are more likely to use IONM as compared to those working in district hospitals. Surgeons who perform less than 100 thyroidectomies were more likely to be users of IONM. Conclusion: IONM is not routinely used in thyroid surgery in Australia and New Zealand. The main reasons for the use of IONM given in our study by routine users were to establish familiarity of equipment and medicolegal reasons. Selective users chose as the most common reasons, a documented pre‐existing unilateral nerve paresis or a hostile surgical field. Non‐users stated that there was conflicting evidence that it improves outcomes and increased costs. Abstract : This article examines the patterns and reasons for usage of intraoperative nerve monitoring in thyroid surgery in Australia and New Zealand.